Using Structured Observation and Content Analysis to Explore the Presence of Older People in Public Fora in Developing Countries - Geraldine Nosowska; Kevin McKee; Lena Dahlberg (Journal of Aging Research)
There is a lack of research on the everyday lives of older people in developing countries. This exploratory study used structured observation and content analysis to examine the presence of older people in public fora and considered the methods’ potential for understanding older people’s social integration and inclusion. Structured observation occurred of public social spaces in six cities each located in a different developing country and in one city in the United Kingdom, together with content analysis of the presence of people in newspaper pictures and on television in the selected countries. Results indicated that across all fieldwork sites and data sources, there was a low presence of older people, with women considerably less present than men in developing countries. There was variation across fieldwork sites in older people’s presence by place and time of day and in their accompanied status. The presence of older people in images drawn from newspapers was associated with the news/non-news nature of the source. The utility of the study’s methodological approach is considered, as is the degree to which the presence of older people in public fora might relate to social integration and inclusion in different cultural contexts.